Scooby-Doo! World of Mystery 49 Scotland - Edinburgh Castle - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
Yikes!The gang visit the most haunted castle in Britain to investigate a ghost with mysterious magical powers...
Keywords: Juvenile literature-Fiction